Survival Aswaja di Alam Melayu Brunei - Ahmad Effendi; Moh. Zainol Kamal (Tafhim Al-'Ilmi, 2021)
Abstract This article is about the survival ASWAJA in the region of Malay Brunei. Ahlussunnah Waljama'ah has become the pulse for the sustainability of the State of Brunei Darussalam. The practice of Ahlussunnah Waljama'ah both as a creed or as an ideology has been carried out in this country since ancient times where a king plays an important role in guarding and disseminating Ahlussunnah Waljama'ah. Ahlussunnah Waljama'ah was strengthened by its inclusion in the Brunei State Institutions Act 1959 AD and was reaffirmed on the independence day of the country of Brunei in 1984 AD, through the decree of the Sultan of Brunei Hassanal Bolkiah on the day of the proclamation of independence of the State of Brunei Darussalam. Kata Kunci; ASWAJA, Melayu Brunei